If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2y + 12) = 4y Reorder the terms: (12 + 2y) = 4y Remove parenthesis around (12 + 2y) 12 + 2y = 4y Solving 12 + 2y = 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 12 + 2y + -4y = 4y + -4y Combine like terms: 2y + -4y = -2y 12 + -2y = 4y + -4y Combine like terms: 4y + -4y = 0 12 + -2y = 0 Add '-12' to each side of the equation. 12 + -12 + -2y = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -2y = 0 + -12 -2y = 0 + -12 Combine like terms: 0 + -12 = -12 -2y = -12 Divide each side by '-2'. y = 6 Simplifying y = 6
| 19+6x=61 | | -7r-3x+2=-8x-8 | | 8(x+2)-3(x-4)=6(x+7)+8 | | 2(x^2-4)=2(3x^2+1) | | -11+3x=10 | | 8/9p-2/3^^^^^^^6_ | | 24+6x=78 | | 2g+8=23 | | n^2-4x+5=0 | | 4x^2-1=7x^2+9 | | (0.5)(-0.5)(3.2)(7.9)(-2.4)= | | -82-8x=22-12x | | .5x^2+7=11 | | 7+2u=2u-9 | | 42/21=14/x | | 10X^2-6=-3 | | 7x+3=8x-10 | | ln(2x-2)=ln(x+8) | | 7x+8=7+5x | | -3(2p+1)1+4(2p-3)=2p-15 | | 2w+4=38 | | 8a-16=8-40 | | 2x+10+x(2)+x(2)=32 | | 5x+10m=7x | | In(5x-9)=3 | | (8x-2)(8x+2)=12 | | 16x^2+36y^2-576=0 | | -2x=x+4 | | 2x+10(2)+x(2)=32 | | Log(6x-98)=2 | | 7g+18=2g+3 | | 3(-x+1)=-3.75(x-2) |